Hubungan Pengetahuan Orang Tua Dengan Kemampuan Toilet Training Anak Usia Dini di Desa Irian Kabupaten Pasaman Barat - Nova, Gema; Ismaniar, Ismaniar (Jurnal Family Education, 2023)
The background of this research is the low toilet training skills of children in Irian Village, West Pasaman Regency, this is allegedly due to the lack of knowledge of parents about toilet training. The purpose of this study is to describe parents' knowledge about toilet training in children, describe toilet training skills in children, and the relationship between knowledge and toilet training skills in early childhood in Irian Village, West Pasaman Regency. This study uses a quantitative approach with a correlational type. The study population, namely children aged 2-3 years in Irian Village, totaled 48 people. The sample for this study was taken as much as 75%, namely 34 people with a stratified random sampling technique. Data collection techniques with questionnaires and data collection tools using a questionnaire containing a list of statements. The data analysis technique in this study uses the percentage and product moment formulas. The results of this study indicate that: 1). The description of parents' knowledge about toilet training is categorized as good 2). The description of toilet training for children aged 2-3 years in Irian Village, West Pasaman Regency, is categorized as not good 3). There is a relationship between parental knowledge and toilet training skills in children aged 2-3 years in Irian Village, West Pasaman Regency, but the relationship is less significant because it is categorized as moderate. It is hoped that parents in Irian Village will increase their children's knowledge about toilet training and pay attention to toilet training in children so that they can carry out the toilet training process properly and correctly. In order for children to carry out the toilet training process properly, correctly and as much as possible, the school environment and the surrounding community must also play a role. Keywords: parents' knowledge of toilet training, toilet training ability